Expression and clinical relevance of paired box protein 7 and sex determining region Y-box 2 in canine corticotroph pituitary adenomas. Issue 3 (June 2015) - van Rijn, Sarah J.; Pouwer, Marianne G.; Tryfonidou, Marianna A.; Grinwis, Guy C.M.; van der Bend, Joanne E.E.; Beukers, Pauline E.P.F.; Vastenhout, Nadie; Drouin, Jacques; Penning, Louis C.; Meij, Björn P.
Highlights: The expression of Pax7 and Sox2 was studied in canine pituitary adenomas. Pax7 expression was higher in enlarged pituitaries than in non-enlarged pituitaries. Downstream targets of Pax7 were significantly down regulated in adenoma samples. Pax7 and Sox2 are unsuitable as clinical prognosticators in canine Cushing's disease. Abstract: Pituitary-dependent hypercortisolism is a common endocrinopathy in dogs, caused by an adrenocorticotrophic hormone secreting pituitary tumour of the anterior or intermediate lobe. The prognosis of intermediate lobe adenomas is worse than that of anterior lobe adenomas, indicating the possible usefulness of melanotropic markers as prognosticators. Another possible origin of pituitary adenomas is found in cancer stem cells. The aim of the present study was to investigate the expression of melanotroph specific transcription factor paired box protein 7 (Pax7) and stem cell marker and reprogramming factor sex determining region Y-box 2 (Sox2) and to relate their expression to clinical parameters. The mean ± SD of labelling index (LI) for Pax7 was 8.6% ± 21.7% in the adenomas; 1/6 controls had positive staining (LI, 15.2%). For Sox2, the LI in the adenomas was 16.9% ± 15.2% and 19.5% ± 11.6% in the controls. Pax7 expression was significantly higher in enlarged pituitaries, compared to non-enlarged pituitaries ( P  = 0.05), but Pax7 or Sox2 immunopositivity did not correlate to other clinical parameters such as histological diagnosis, survival time or disease-free interval. Gene expression of Pax7 target genes, such as proconvertase 2 ( PC2 ), pro-opiomelanocortin ( POMC ), and dopamine D2 receptor ( DRD2 ), was significantly lower in the adenoma samples compared to normal tissue, indicating that Pax7 signalling was not activated in adenomas. It was suggested that Pax7 and Sox2 remain interesting targets for molecular investigations into their role in pituitary tumorigenesis, but were unsuitable as clinical prognosticators in dogs.